Home Sweet Home: Plasmodium vivax-Infected Reticulocytes—The Younger the Better? - Thomson-Luque, Richard; Bautista, José M. (Frontiers in Cellular and Infection Microbiology, 2021)
After a century of constant failure to produce an in vitro culture of the most widespread human malaria parasite Plasmodium vivax, recent advances have highlighted the difficulties to provide this parasite with a healthy host cell to invade, develop, and multiply under in vitro conditions. The actual level of understanding of the heterogeneous populations of cells—framed under the name ‘reticulocytes’—and, importantly, their adequate in vitro progression from very immature reticulocytes to normocytes (mature erythrocytes) is far from complete. The volatility of its individual stability may suggest the reticulocyte as a delusory cell, particularly to be used for stable culture purposes. Yet, the recent relevance gained by a specific subset of highly immature reticulocytes has brought some hope. Very immature reticulocytes are characterized by a peculiar membrane harboring a plethora of molecules potentially involved in P. vivax invasion and by an intracellular complexity dynamically changing upon its quick maturation into normocytes. We analyze the potentialities offered by this youngest reticulocyte subsets as an ideal in vitro host cell for P. vivax.